TIKTOK ADVERTISING AND REPURCHASE INTENTION: THE MEDIATING ROLE OF BRAND AWARENESS AND BRAND IMAGE WITHIN THE S–O–R FRAMEWORK - Kurniawati; Fairuz Faradina; Yolanda Masnita (Majapahit Journal of Islamic Finance and Management, 2026)
This study examines the effect of TikTok advertising on repurchase intention by analyzing the mediating role of brand perception within the Stimulus–Organism–Response (S-O-R) framework. Using a quantitative approach, data were collected from 233 Indonesian TikTok users with prior purchasing experience and analyzed using Structural Equation Modeling (SEM) with the Maximum Likelihood Estimation method. The findings show that content quality and engagement in TikTok advertising have a positive and significant effect on brand perception. However, these advertising attributes do not directly influence repurchase intention. Further analysis indicates that brand perception fully mediates the relationship between TikTok advertising and repurchase intention, suggesting that repeat purchase behavior is formed through consumers’ internal evaluation processes rather than direct advertising exposure. This study extends the application of the S-O-R framework to short video–based digital marketing and provides practical insights for firms seeking to strengthen long-term consumer retention through effective brand-building strategies.